Bacterial blight, caused by Burkholderia glumae, is attacking Brachiaria in Colombia: First report - Álvarez, Elizabeth; Latorre, Michael A. (Scientific Societies, 2017)
In 2009, a bacterial blight was observed in a greenhouse at CIAT headquarters, attacking plants of Brachiaria humidicola. Because Brachiaria grasses are grown as pastures throughout South America, this new disease could, potentially, have significant economic implications. Symptoms included chlorotic streaks, necrosis, and yellowing of flag-leaf margins. Isolates cultured onto King’s B medium were cream-colored, producing a yellow, diffusible, non-fluorescent pigment. For molecular identification, the 16S rDNA gene was amplified from all isolates, using primers 27f and 1525R, and obtaining a PCR product of 1500 bp. The nucleotide sequences were 99% identical to those of GenBank accession no. CP009435.1 and other entries of Burkholderia glumae. To confirm pathogenicity, 10 plants were inoculated by injection with bacterial suspensions at 108 cfu/mL for each of nine genotypes: B. decumbens CIAT 606; B. brizantha cv. Marandu; B. brizantha cv. Toledo; B. ruziziensis CIAT 4402; CIAT 36061 cv. Mulato I, CIAT 36062, CIAT 36087 cv. Mulato II, BR02/1752, and BR02/1794. Control plants received sterilized distilled water. All the plants were incubated in microchambers, placed in a greenhouse at 28°C, and evaluated 6 days after inoculation. Inoculated plants showed chlorotic streaks, necrotic lesions, and a yellowing flag leaf. Control plants showed no symptoms. This is the first report on Burkholderia glumae causing bacterial blight in Brachiaria in Colombia.